A study of syndromic and etiological approach for the diagnosis of reproductive tract infections - Saharan, Surbhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Reproductive tract infections (RTIs) are one of the most common and major health problem around the world and they are much more widespread in developing countries than in developed countries due to Inadequate health services. Methods: Detailed history including, menstrual, obstetric and sexual history of the patients were taken and general, physical and local examination was done and clinical symptoms and sign were noted using a structured screening proforma. Results: In our study syndromic approach has a moderate diagnostic accuracy in detecting vaginal discharge syndrome and pain abdomen syndrome. Syndromic diagnosis is low cost effective, more acceptable and easily available at primary and secondary health centre. It should be continued as first line management. Conclusions: In present study the vaginal discharge syndrome has sensitivity of 64.71% and specificity of 57.14%, PPV 61.11%, NPV 60.87% and accuracy is 61%. If treatment is given only on the basis of syndromic approach for vaginal discharge syndrome it results in over-treatment in 42.86% (false positive) and under diagnosis in 35.29% (false negative). This approach was found less effective. For lower pain abdomen syndrome the sensitivity is 21.74% and specificity is 84.62%, PPV 38.46%, NPV 70.97% and accuracy is 65.33%. If treatment is given only on the basis of syndromic approach for lower pain abdomen syndrome results in over -treatment in 15.38% (false positive) and under diagnosed 78.26%.(false negative). This approach was found less effective.